A high frame rate image acquisition system for dynamic centrifuge tests. Issue 1 (March 2001) - Okamura, Mitsu; Matsuo, Osamu; Tamoto, Shuichi
Abstract : A high frame rate image acquisition system for dynamic centrifuge tests developed at Public Works Research Institute is described. The image acquisition and processing technique provide not only residual deformations but also the cyclic component of deformation. In order to verify the performance of the developed system a dynamic centrifuge test was conducted where both the high frame rate image recording and displacement measurements were made. The results of this calibration test showed that the deformation of target markers derived from image analysis compared fairly well with that obtained from direct measurement by displacement transducers.